Female Brass Musicians Address Gender Parity, Gender Equity, and Sexual Harassment: A Preliminary Report on Data from the Brass Bodies Study - Schmalenberger, Sarah; Maddox, Patricia (Societies, 2019)
The Brass Bodies Study is an exploratory cross-sectional study designed to describe and understand the experience of female brass players. This report discusses selected data from close-ended and open-ended responses to questions regarding gender equity, parity, and sexual harassment within a web-based survey that launched the first phase of the study. The survey queried subjects’ physical changes to their brass playing due to various catalysts: life-cycle events; injury, illness, harassment, mental health, racism, and homophobia. The survey instrument further queried whether subjects received support about these changes and the effectiveness of support. The following report discusses survey responses to questions about gender parity and changes to brass playing due to sexual harassment. Additional qualitative data were generated from open-ended questions in the survey and were qualitatively coded and thematically presented to supplement the descriptive statistics provided. The information presented explores and defines salient items and themes of a population that is under researched with the hopes of generating hypotheses for continued research.
Keywords: Brass Bodies Study; Myriam; female brass players; female musicians; music workplace climate